A descriptive study to assess the knowledge and practices related to cough and sneeze etiquette among health care providers, respiratory patients and their attendants in a tertiary care centre - Kumar, Arjun; Janmeja, Ashok Kumar; Manchanda, Rohit; Singh, Balbir; Lakra, Ankit; Gupta, Rahul (International Journal Of Community Medicine And Public Health, 2023)
Background: The emergence of respiratory infections including Tuberculosis, COVID-19, influenza A and B viruses have a significant impact on health worldwide. Cough and sneezing etiquette including respiratory hygiene have been recommended as most cost-effective preventative tool to reduce such transmission. Methods: A cross-sectional descriptive study was conducted among health care providers, respiratory patients and their attendants admitted in the Respiratory Medicine department at a tertiary care hospital for 6 months duration i.e., from December 2022 to May 2023, aiming to assess the knowledge and practices related to cough and sneeze etiquette. A total of 200 study subjects were interviewed with the help of a semi-structured questionnaire. The study findings were recorded and analyzed using SPSS version 20. Results: Out of 200 subjects, most 95 (47.5%) of subjects belonged to the age group between 40 to 60 and 109 (54.5%) were females and 91 (45.5%) were male. Majority of the participants were medical students; 62 (31%) followed by paramedical staff; 49 (24.5%), laborers and doctors; 26 (13%). Only 88 (44%) participants had heard about cough etiquette. Most common source of information regarding the proper cough and sneeze etiquette among the participants was television or internet;112 (61%). The patients and their attendants were having poor knowledge regarding the proper cough and sneeze etiquette. Conclusions: The knowledge and practice of cough and sneezing etiquette was not satisfactory especially among the general population. There is the utmost need for awareness regarding the knowledge and correct practice of cough etiquette.